Peran Hukum saat Pandemi sebagai Terobosan dalam Mewujudkan Kesejahteraan Masyarakat - Shinta Rukmi Rukmi Budiastuti; Isnaini Apri Dawati (LOGIKA : Jurnal Penelitian Universitas Kuningan, 2021)
The role of law during a pandemic affects what the government will do in disaster prevention and management as a breakthrough in realizing the welfare of society amid Covid-19. Given that Indonesia adheres to the concept of a walfare state which affects the welfare of the community where the government is more dominant in creating welfare. However, in needing the government, it requires a standard or basis, that basis is law. This proves that the law of human assistance, including the government in realizing prosperity during this pandemic, so that indirectly the law has an impact on the welfare of the community. As a result of this pandemic many people feel that their welfare is reduced, to overcome all that, various legal products are published as breakthroughs. To overcome the impact from economic, health, and other aspects, an example of a legal product related to impact management in the economic sector is the arrangement for the allocation of village funds through the direct cash assistance program (BLT) provided to the community with criteria for the poor based on data from the government and the allocation of village funds which was originally going to be used for development as infrastructure to be transferred to activities to handle the covid-19 pandemic outbreak as stated in Presidential Decree Number 54 of 2020.Peran hukum disaat pandemi berpengaruh terhadap apa yang akan dilakukan pemerintah terkait pencegahan dan penanggulangan bencana sebagai trobosan mewujudkan kesejahteraan masyarakat ditengah covid-19. Mengingat Indonesia meganut Konsep walfare state yang berpengaruh terhadap kesejahteraan masyarakat dimana pemerintahlah yang lebih dominan dalam mewujudkan kesejahteraan. Namun dalam bertindak pemerintah memerlukan adanya sebuah patokan atau dasar, dasar tersebut adalah hukum. Hal ini membuktikan bahwa hukum mengatur tindak manusia termasuk pemerintah dalam mewujudkan kesejahteraan di masa pandemi ini,sehingga secara tidak langsung langsung hukum memberikan dampak terhadap kesejahteraan masyarakat.Akibat adanya pandemi ini banyak masyarakat yang merasakan kesejahteraannya berkurang ,untuk  mengatasi itu semua maka diterbitkanlah berbagai produk hukum sebagai trobosan untuk mengatasi dampak dari aspek ekonomi, kesehatan , dan lain sebagainya ,contoh produk hukum terkait penanngulangaan dampak dibidang ekonomi adalah pengaturan   pengalokasian dana desa melalui program (BLT) Bantuan Langsung Tunai yang diberikan kepada masyarakat dengan kriteria masyarakat miskin bedasarkan data dari pemerintah serta pengalokasian dana desa yang semula akan diperguanakan sebagai pembangunan infrasruktur dialihkan  untuk  kegiatan penanganan wabah  pandemi covid-19 sesuai dengan yang termuat didalam Perpres Nomor 54 tahun 2020 .